(3fRgI GdCee aj GdYLGFH hGdMces - (3eMeO Hf CMeO Hf EjGS GdMfaj GdeUQj, CHh GdHQcGJ,J (B930 (3g` s ((3eMeO Hf ESeGYjd GdebOSj s)
(3ChdgG (B:s
(3GdMeO ddg GdPi YQa hage , hYde GdEfSGf eGde jcf jYde s
(3Yf fSNI HNW GdeDdas
(3jdjgG ChQGb ai PcQ HfGA eOjfI GdaSWGWs
(3gfGc fSNI CNQi HYfhGf (B"(3fTb GdCRgGQ ai YLGFH GdCbWGQ HQbe (B" 1288"s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs